2016
DOI: 10.1039/c6ra06468j
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric fluorescent pH-sensitive polymers for high-throughput monitoring of extracellular pH

Abstract: Extracellular pH has a strong effect on cell metabolism and growth. Precisely detecting extracellular pH with high throughput is critical for cell metabolism research and fermentation applications. In this research, a series of ratiometric fluorescent pH sensitive polymers are developed and the ps-pH-neutral is characterized as the best one for exculsive detection of extracellular pH. Poly(N-(2-hydroxypropyl)methacrylamide) (PHPMA) is used as the host polymer to increase the water solubility of the pH sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 67 publications
(100 reference statements)
0
20
0
Order By: Relevance
“…AIE emission was detected at 520 nm and PtTFPP emission was measured at 650 nm. The measurement was carried out at 37 • C. Previously, we have showed that similar PHPMA copolymers were cell impermeable for a few cell lines, like E. coli and HeLa cell lines [63]. For avoiding the exchange of oxygen in the cell culture medium with air, a thin layer of mineral oil was added on the top of the LB medium.…”
Section: Cell Respirationmentioning
confidence: 99%
“…AIE emission was detected at 520 nm and PtTFPP emission was measured at 650 nm. The measurement was carried out at 37 • C. Previously, we have showed that similar PHPMA copolymers were cell impermeable for a few cell lines, like E. coli and HeLa cell lines [63]. For avoiding the exchange of oxygen in the cell culture medium with air, a thin layer of mineral oil was added on the top of the LB medium.…”
Section: Cell Respirationmentioning
confidence: 99%
“…With high accuracy, any suspension culture of mixed populations could be maintained in log phase growth for days in order to study transient invaders into microbial communities 33 or even microbiome system dynamics 34 . The advent of small molecule fluorescent reporters for metabolic fitness 35 , pH 36,37 , and CO2 38 , in addition to the hundreds of fluorescent protein sensors available to the synthetic biology community at large 39,40 , also impresses the seemingly unlimited potential of being able to multiplex and quantify changes in growth, gene expression, and the environment in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…This UPR response is activated to lower the misfolded or unfolded protein content. When ER stress becomes intense, the UPR response shifts to autophagic and pro-apoptotic signaling capabilities ending in cell death (32,33). To ascertain fidelity to correct protein folding, cells regulate protein-folding capacity in the ER according to need.…”
Section: Discussionmentioning
confidence: 99%
“…This means that curcumin's induction of the cellular antioxidant system and/or efficient mitophagy associated with restoration of ∆Ψm may push almost 50% of cells to go through the cell cycle and escape cell death. It is quite interesting to hypothesize that the alteration of lysosomes and activation/delocalization of TFEB may lead to mitochondrial biogenesis (33). In parallel, this is also associated with an increased level of mitophagy and overall this results in a restored quality of mitochondrial functions (33).…”
Section: Successful Curcumin-induced Autophagy Detected By Impedancemmentioning
confidence: 99%
See 1 more Smart Citation